2020
DOI: 10.1111/jdv.16333
|View full text |Cite
|
Sign up to set email alerts
|

Evidence supporting the enhanced efficacy of pentavalent antimonials with adjuvant therapy for cutaneous leishmaniasis: a systematic review and meta‐analysis

Abstract: Cutaneous leishmaniasis (CL) is one of the major neglected disease worldwide. Although many drugs have been used, the pentavalent antimonials (PA) remain as the first-line choice despite their toxicity and limited efficacy. The combination of two drugs has risen as a potential alternative to increase the cure rate while lowering the side-effects caused by pentavalent antimonials (PA). The objective of this study was to critically review and appraise the potential synergism of the adjuvant therapies of PA with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…4 Despite the lack of robust clinical trials, including high-level randomized clinical trials, multiple case reports and retrospective data have demonstrated their efficacy. 12…”
Section: Discussionmentioning
confidence: 99%
“…4 Despite the lack of robust clinical trials, including high-level randomized clinical trials, multiple case reports and retrospective data have demonstrated their efficacy. 12…”
Section: Discussionmentioning
confidence: 99%
“…Some in vivo and in vitro 10 reports have shown the effect of topically applied imiquimod on cutaneous leishmaniasis 10 - 12 . However, a recent systematic review established that imiquimod has no significant therapeutic effect when combined with antimonials 13 . Our patient achieved complete recovery after topical imiquimod treatment without previous treatments, and no relapse was observed after a 2-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The meta‐analysis was performed with the Review Manager software (RevMan 5.3.5) as previously described 9 …”
Section: Methodsmentioning
confidence: 99%